Admiral: a 19th‐century Tyne‐built paddle tug. (7th August 2019) - Croce, Paolo; Gane, Toby
Abstract: This paper reports on the discovery in the Thames Estuary and the partial recovery and recording of the remains of a 19th‐century Tyne‐built paddle tug. The wreck is believed to be that of Admiral built in Newcastle in 1870 and sunk following a collision in the estuary in 1872. This unexpected discovery provided a rare opportunity to examine the archaeological assemblage of one these once‐familiar working vessels and revealed the continuities and innovations of a specific type of engine used on paddle tugs. Abstracto: Admiral : un vapor remolacador a palteas construido en el siglo XIX en los astilleros del Río Tyne Este artículo reporta sobre el descubrimiento, registro y recuperación parcial de los restos de un vapor remolcador a paletas construido en el siglo XIX en los astilleros del Río Tyne y hallado en el Estuario del Támesis. Se cree que se trata del pecio del Admiral construido en Newcastle en 1870 y hundido tras una colisión en el estuario en 1872. Este descubrimiento inesperado proporciona la oportunidad poco común de examinar los restos arqueológicos de una de estas embarcaciones de trabajo que alguna vez fueron familiares y revelar las continuidades e innovaciones de un tipo específico de motor empleado en los vapores remolcadores a paletas. 抽象: "海军上将"号——十九世纪的泰恩造桨式拖船 本文记述的是一艘发现于泰晤士河口的十九世纪泰恩造桨式拖船。该残骸已得到部分修复并记录在册。此沉船被认为是1870年建于纽卡斯尔的"海军上将"号 ( Admiral), 其于1872年在泰晤士河口被撞沉。此次意外发现不仅为我们提供了一次难得的机会得以从考古组合角度研究这些曾经熟悉的工作船只中的一员, 它还向我们揭示了用于桨式拖船的特定类型引擎的连续性及其变革。 "海軍上將"號——十九世紀的泰恩造槳式拖船 本文記述的是一艘發現于泰晤士河口的十九世紀泰恩造槳式拖船。該殘骸已得到部分修複並記錄在冊。此沉船被認爲是1870年建于紐卡斯爾的"海軍上將"號 ( Admiral), 其于1872年在泰晤士河口被撞沈。此次意外發現不僅爲我們提供了一次難得的機會得以從考古組合角度研究這些曾經熟悉的工作船只中的一員, 它還向我們揭示了用于槳式拖船的特定類型引擎的連續性及其變革。 ملخص: